Study on Dynamic Changes of Dew Point Air Temperature at the Attachment Layer of Radiant Ceiling - Jin Wufeng; Bi Chen; Gao Pan; Jia Lizhi; Wang Zhiqiang (Zhileng xuebao)
The variation in dew point temperature at the attached layer of radiant ceiling was examined when the number of indoor occupants was increased in this study. Through numerical simulation and linear regression performed by SAS software, the influence of various factors on the air dew point temperature of the attached layer was obtained. Furthermore, the dynamic relationship between the main influence factor and the dew point temperature of the attached layer was obtained, and the experimental data was used to verify the simulation and calculation results. The results show that the air dew point temperature increased by approximately 1.5 °C and 2.5 °C when adding two and four people, respectively. The distance between the personnel and the attached layer, as well as the number of personnel have a great influence on the dew point temperature of the attached layer, with the contribution rate accounting for 43% and 48%, respectively; and the contribution from the other impact factors can be ignored. The dynamic change of the air dew point temperature of the attached layer is in the form of a negative exponential function. The influence of the distance between the attached layer and the personnel on the dew point temperature of the attached layer is greater than that of the increase in personnel number.